Denosumab-treated Giant Cell Tumors of Bone: A Clinicopathologic Analysis of 35 Cases From the French Group of Bone Pathology. (January 2020) - Treffel, Mathilde; Lardenois, Emilie; Larousserie, Frédérique; Karanian, Marie; Gomez-Brouchet, Anne; Bouvier, Corinne; Le Loarer, François; Aubert, Sébastien; de Pinieux, Gonzague; Audard, Virginie; Rios, Maria; Sirveaux, François; et al.
Abstract : Denosumab, an antibody directed against receptor activator of nuclear factor-κB ligand (RANKL), has recently been introduced in the treatment strategy of giant cell tumor of bone. In this study, we assessed the tumor changes induced by denosumab in a national multicentric series of 35 cases (French Bone Pathology Group network—ResOs). Tissue specimens collected before and after denosumab treatment were investigated for RANKL, H3.3 G34W, p63, and Ki-67 expression, and for H3F3A mutation. These parameters were put in correspondance with clinical and radiologic presentation to identify prognostic factors, and more specifically, predictive markers of an optimal histologic response to denosumab, identified as a ≥50% loss in giant cells with fibrosis and ossification. The main changes in posttreatment specimens showed an induction of ossification ( P =2.10 −5 ), an increased fibrosis ( P =3.10 −5 ), and a major decrease in giant cells ( P =6.10 −11 ). No significant change in mononuclear tumor cell density and in patterns of expression of RANKL ( P =0.061) and H3.3 G34W was observed ( P =0.061). An optimal histologic response to denosumab treatment was associated with an enhanced progression-free survival ( P =0.010 in univariate analyses; P =0.040 in multivariate analyses). The initial number of giant cells was predictive of the histologic response to treatment ( P =0.016). In summary, denosumab treatment induced radical changes in the tumor. The histologic response, despite the absence of objective regression of the mononuclear cells, was associated with an enhanced progression-free survival. Greater numbers of giant cells represented the only predictive indication of an optimal histologic response to denosumab treatment. Abstract : Supplemental Digital Content is available in the text.